A reliable testing battery for assessing physical qualities of elite academy rugby league players - Dobbin, N.; Hunwicks, R.; Highton, J.; Twist, C. (The Journal of Strength and Conditioning Research, 2018)
This study assessed the interday reliability of a testing battery for the assessment of physical qualities of rugby league players. Fifty players (age 17.1 ± 1.1 years; stature 181.3 ± 6.3 cm; and body mass 89.0 ± 11.6 kg) from 3 Super League academies participated in this study. Tests of countermovement jump performance, 10- and 20-m sprint performance, change of direction, medicine ball throw, and a modified Yo-Yo Intermittent Recovery Test Level 1 (prone Yo-Yo IR1) were completed on 3 separate occasions. Between-day intraclass correlation coefficient, typical error (TE), coefficient of variation, and the smallest worthwhile change (SWC) were calculated to determine the reliability and sensitivity of each measure. Individual tests (except medicine ball throw) were not systematically different between trials (p > 0.05), with an interday variability that was <10%. In all instances, the TE was larger than the calculated SWC change, although variability was less than that typically observed after a training intervention or specific training period (i.e. preseason). Using a magnitude-based inference approach, we present the required change for all performance tests to be 75% confident and the change is beneficial. This simple and time efficient testing battery is sufficiently reliable to detect previously observed changes in a range of physical qualities of rugby league players.